Rituali della giustizia e paradossi della verità in alcune novelle di Verga - Lo Castro, Giuseppe (Studia Romanica Posnaniensia, 2014)
The present paper focuses on a selection of Giovanni Verga’s short tales (Un processo, Tentazione!, Quelli del colèra, Cos’è il re, Il reverendo, La chiave d’oro, Don Licciu Papa), by analyzing his nonstereotypical enquiry into the close relationship between power forms and practices of justice.